Profiles of colour, minerals, amino acids and fatty acids of musculus longissimus thoracis et lumborum of Ghungroo pigs - THOMAS, R; BANIK, S; BARMAN, K; MOHAN, N H; SARMA, D K (The Indian Journal of Animal Sciences, 2016)
Carcass composition and meat quality were evaluated in Ghungroo, the first registered indigenous pig breed of India. Ghungroo pigs (16 gilts and 26 barrows) were slaughtered at the age of 10 months for evaluating the different parameters. Instrumental colour measurement indicated that the coordinates were in the following range: lightness (L*), 39.17 - 57.39; redness (a*, red ± green), 8.37 - 14.21; and yellowness (b*, yellow ± blue), 13.08 - 18.17. Haem iron content was significantly higher in barrows compared to gilts. The mineral contents in the musculus (M.) longissimus thoracis et lumborum were in the following range: potassium, 289 – 349 mg/100g; zinc, 0.58 – 0.91 mg/100g; copper, 0.13 – 0.17 mg/100g; manganese, 0.05 –0.06 mg/100g and magnesium, 4.72 –7.37 mg/ 100g. Significant differences were not observed in the concentration of any of the estimated amino acids between the sexes. Fatty acid profiling of M. longissimus thoracis et lumborum indicated that saturated and unsaturated fatty acids were in the range of 32.17 - 41.19% and 58.98 - 68.15%, respectively. Results further indicated a concentration of 0.88 – 1.73% omega-3 fatty acids; 19.95 - 27.23% omega-6 fatty acids and 14.52 - 23.47% essential fatty acids in the Ghungroo muscle tissues.